1996
DOI: 10.1007/bf02071404
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of gallbladder disease in diabetes mellitus

Abstract: A study was undertaken to compare the prevalence of gallstone disease (gallstones observed on ultrasound or history of cholecystectomy) in 308 diabetics and 318 controls. There was a higher prevalence of gallstone disease (GSD) in diabetics (32.7%) compared to controls (20.8%; P < 0.001 chi-squared test). However, when gender was taken into account, the difference was only significant in females (diabetics 41.8% versus controls 23.1%; P < 0.001). Analysis by type of diabetes revealed that subjects with non-ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
59
4
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 29 publications
16
59
4
4
Order By: Relevance
“…Our findings are in agreement with previous cross-sectional and prospective studies of serum lipids and gallstones, which have consistently reported high triglycerides and low HDL in association with gallstone risk. [5][6][7]18,19 Paradoxical to the generally accepted association between hyperlipidemia and gallstones, we observed that lower levels of total cholesterol, LDL and apo B, characteristic of hypolipidemia, were also associated with biliary stones, independently of the other lipids and risk factors we examined. High levels of total cholesterol, LDL and apo B were not associated with biliary stones.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in agreement with previous cross-sectional and prospective studies of serum lipids and gallstones, which have consistently reported high triglycerides and low HDL in association with gallstone risk. [5][6][7]18,19 Paradoxical to the generally accepted association between hyperlipidemia and gallstones, we observed that lower levels of total cholesterol, LDL and apo B, characteristic of hypolipidemia, were also associated with biliary stones, independently of the other lipids and risk factors we examined. High levels of total cholesterol, LDL and apo B were not associated with biliary stones.…”
Section: Discussionmentioning
confidence: 99%
“…The most common etiologies of acute pancreatitis accounting for 70-80% of cases are alcohol and gallstones. Chapman reported in 1996 a higher prevalence of gallstone disease based on ultrasound examination or report of cholecystectomy in diabetics (32.7%) compared to controls (20.8%, p<0.001) (Chapman, 1996). The difference was even greater for females were prevalence was 41.8% for female diabetic compared to controls 23.1% (p<0.001).…”
Section: Diabetes and Acute Pancreatitismentioning
confidence: 97%
“…Jorgensen failed to find an increased prevalence of gall stones in diabetic subjects in a Danish population after adjusting for obesity in a population not known for insulin resistance (Jorgensen). Chapman, in contrast, found an increased risk for gallstones in female diabetic subjects in New Zealand but no statistically increase in male diabetics after controlling for other know risk factors of BMI, HDL cholesterol, and TG, common comorbidities associated with type 2 diabetes (Chapman, 1996). Chapman reported increased gallbladder volume in type 2 diabetic subjects even without stones not seen in type 1 diabetics (Chapman 1998).…”
Section: Diabetes and Acute Pancreatitismentioning
confidence: 99%
“…A study from New Zealand reported a gallbladder stones prevalence of 32.7% among diabetic patients as compared to 20.8% in controls. 56 Another study from Italy showed that the prevalence of gallstone disease is significantly higher in diabetic patients than in the general population (24.8 vs. 13.8%). 57 The prevalence of gallstone was 40% among Libyan diabetic individuals and correlate positively with age and obesity.…”
Section: Cholesterol Gallstones and Renal Stone Disease And Diabetesmentioning
confidence: 97%